Objective and Subjective Measures of Socioeconomic Status Are Associated with Metabolic Syndrome Severity Among African American Adults in the Jackson Heart Study (P18-006-19). (13th June 2019) - Cardel, Michelle; Guo, Yi; Sims, Mario; Dulin, Akilah; Miller, Darci; Pavela, Gregory; Deboer, Mark; Gurka, Matthew
Abstract: Objectives: In this study, data from the Jackson Heart Study (JHS) were used to assess the independent associations between objective socioeconomic status (OSS) and subjective social status (SSS) with metabolic syndrome (MetS) severity and MetS indicators in African American (AA) adults at baseline and eight years later. Methods: Participants included 3870 AA participants (63.1% women; mean age 53.8 ± 13.0, age range 35–84 years). OSS was assessed using annual household income and years of school completed. SSS was measured with the MacArthur Scale, using two 10-rung "ladders" with U.S. society and the individual's community as referent groups for their perceived social rank. Associations of OSS and SSS with a sex- and race/ethnic-specific MetS severity Z-score were examined after adjustment for demographics and MetS risk factors (i.e., nutrition, physical activity, smoking status, and alcohol consumption) at baseline and 8-year follow-up. Results: Independent of OSS, demographic, and lifestyle factors, individuals who placed themselves on lower rungs of a visual ladder depicting relative social standing in society had more severe metabolic syndrome at baseline but not 8-years later ( P  = 0.0123 and P  = 0.3248, respectively). The components of MetS driving the relationship between US-level SSS and MetS severity at baseline were waist circumference and triglyceride levels, as waist circumference and triglycerides at baseline were inversely associated with US-level SSS ( P  = 0.0124 and P  = 0.0074, respectively). OSS components, including measures of income and education, were both independently associated with MetS severity at baseline ( P  < 0.05) but not at 8-year follow-up. Community-level SSS was not associated with MetS severity at baseline or 8-year follow-up. Conclusions: These data indicate that both subjective and objective measures of social status are independently associated with cardiometabolic risk factors and the severity of MetS among AA adults and should be considered in adjunct when exploring the role of social determinants of cardiometabolic health. Funding Sources: This work was supported by the National Institutes of Health National Heart, Lung, and Blood Institute (R01HL120960 R25HL126146 and K01HL141535) and the National Center For Advancing Translational Sciences of the National Institutes of Health (UL1TR001427).